Effects of Slope Position on Soil Physico-chemical Characteristics Under Oil Palm Plantation in Wet Tropical Area, West Sumatra Indonesia - Yasin, Syafrimen; Yulnafatmawita, Yulnafatmawita (AGRIVITA, Journal of Agricultural Science, 2018)
This research was aimed to study soil physico-chemical properties at four slope positions under oil palm plantation in Dharmasraya, West Sumatra, Indonesia. Soils were sampled at 0-20 cm soil depth from 4 different slope positions (upper, middle, lower slope, and the bottom or flat area). The parameters analyzed were soil texture, SOM, bulk density, total pore, hydraulic conductivity, soil water potential (physical characteristics) as well as soil pH, CEC, Al-exchangeable, basic cations (Ca, Mg, K), N, and P (chemical characteristics). The results showed that the bottom area had better soil physicochemical properties than the others. SOM increased by 33%, total pore by 19%, void ratio by 47%, plant available water (PAW) by 28%, soil pH-H2O by 41%, CEC by 171 %, total-N by 170 %, and P-potential by 114 %, in contrast, soil BD and exchangeable-Al were lower (20 % and 96 %, respectively) in the bottom than in the sloping land. The middle slope had the poorest soil physico-chemical properties after 26 years of forest conversion into oil palm plantation. All sites had clay texture, the clay content increased (R2=0.93) by lowering slope position, and so did SOM content (R2=0.86), soil CEC (R2=0.93), and soil total-N values (R2=0.76).